Dystocia Due to Schistosomus Reflexus in a Jersey Crossbred Heifer Delivered by Caesarean Section - Periyannan, Mani; Selvaraju, Mani; Gopikrishnan, Duraisamy; Senthilkumar, Krishnamurthy; Varudharajan, Venkatraman; Ravikumar , Kaliannan (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Schistosomus reflexus is a fatal congenital disability and has some peculiar anatomical features such as spinal inversion, exposure of abdominal viscera through the ventral abdominal fissure, limb ankylosis, abnormal positioning of limbs adjacent to the skull, and hypoplasia of thoracic organs and diaphragm (Windsor, 2019). It is a common fetal congenital disorder in ruminants (Selvaraju et al., 2010), but occurrences were rare in heifers (Varudharajan et al., 2019). The present report explains the successful management ofdystocia due to Schistosomus reflexus in a Jersey crossbred heifer by Caesarean section.